2006
DOI: 10.1016/s0929-6646(09)60267-9
|View full text |Cite
|
Sign up to set email alerts
|

Poor Renal Outcome of Antineutrophil Cytoplasmic Antibody Negative Pauci-immune Glomerulonephritis in Taiwanese

Abstract: This study illustrates the necessity for pathologic diagnosis of pauci-immune GN despite ANCA negativity. The poor prognosis associated with ANCA negativity in this study may be partly due to delayed diagnosis since these patients frequently lacked systemic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
40
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 18 publications
12
40
1
2
Order By: Relevance
“…Evaluation of larger cohorts from both the European Vasculitis Study Group and the Chapel Hill Group implied that approximately 10 -30% of patients with pauci-immune crescentic glomerulonephritis lack positive ANCAs (21,22). In both the Taiwanese and the Chinese case series, ANCA-negative pauci-immune crescentic glomerulonephritis presented at a much younger age than those with ANCA-positive disease (19,20). For example, ANCA-negative patients were usually much younger than the ANCA-positive patients (mean Ϯ SD age 45.1 Ϯ 13.5 versus 59.1 Ϯ 17.6 years [19] and 39 Ϯ 17 versus 56 Ϯ 14 years [20]).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Evaluation of larger cohorts from both the European Vasculitis Study Group and the Chapel Hill Group implied that approximately 10 -30% of patients with pauci-immune crescentic glomerulonephritis lack positive ANCAs (21,22). In both the Taiwanese and the Chinese case series, ANCA-negative pauci-immune crescentic glomerulonephritis presented at a much younger age than those with ANCA-positive disease (19,20). For example, ANCA-negative patients were usually much younger than the ANCA-positive patients (mean Ϯ SD age 45.1 Ϯ 13.5 versus 59.1 Ϯ 17.6 years [19] and 39 Ϯ 17 versus 56 Ϯ 14 years [20]).…”
Section: Discussionmentioning
confidence: 94%
“…In both the Taiwanese and the Chinese case series, ANCA-negative pauci-immune crescentic glomerulonephritis presented at a much younger age than those with ANCA-positive disease (19,20). For example, ANCA-negative patients were usually much younger than the ANCA-positive patients (mean Ϯ SD age 45.1 Ϯ 13.5 versus 59.1 Ϯ 17.6 years [19] and 39 Ϯ 17 versus 56 Ϯ 14 years [20]). However, in a study in the UK, no major differences in age at presentation were found between these 2 groups (19).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations